Factors Influencing Employee Performance At Pt. Fokus Inovasi Terpadu - et. al., Indra Taruna Anggapradja, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine how the effect of Organizational Communications. The research method used in this research is descriptive and verification methods. The population in this study is a Employee’s PT Fokus Inovasi Terpadu.The sampling technique used in the study sample size of 38 respondents. While the method of analysis used in this study is simple linear regression analysis, and the coefficient of determination at a significant level of 5%.The results showed that Organizational Communications and Work Motivation had an effect on Performance Employee’s PT Fokus Inovasi Terpadu partially and simultaneously. Communication Organizational and Work Motivation was 54.6% on Performance Employee’s, while the remaining 45.4% was contributed by other variables.